2022
DOI: 10.1021/acs.nanolett.2c01979
|View full text |Cite
|
Sign up to set email alerts
|

Improving Photoelectric Conversion with Broadband Perovskite Metasurface

Abstract: The miniaturization and integration of optoelectronic devices require progressive size reduction of active layers, resulting in less optical absorption and lower quantum efficiency. In this work, we demonstrate that introducing a metasurface made of hybrid organic−inorganic perovskite (HOIP) can significantly enhance broadband absorption and improve photonto-electron conversion, which roots from exciting Mie resonances together with suppressing optical transmission. On the basis of the HOIP metasurface, a broa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…47−49 Various fabrication methods have been employed to create these micro/nano perovskite arrays on bulk materials, including epitaxy growth, 50−52 template-assisted imprinting, 53 and focused ion beam assisted etching. 54 These methods have helped to realize excellent perovskite micro-/nanostructure devices successfully, releasing their potential for a variety of applications in optoelectronics and other fields. He et al grew a single-crystal MAPbI 3 film on a freshly cleaved mica substrate and fabricated perovskite arrays by etching a 200 nm thick MAPbI 3 film using focused ion beam milling with an etching depth of approximately 100 nm.…”
Section: Processing Micro/nano Perovskite Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…47−49 Various fabrication methods have been employed to create these micro/nano perovskite arrays on bulk materials, including epitaxy growth, 50−52 template-assisted imprinting, 53 and focused ion beam assisted etching. 54 These methods have helped to realize excellent perovskite micro-/nanostructure devices successfully, releasing their potential for a variety of applications in optoelectronics and other fields. He et al grew a single-crystal MAPbI 3 film on a freshly cleaved mica substrate and fabricated perovskite arrays by etching a 200 nm thick MAPbI 3 film using focused ion beam milling with an etching depth of approximately 100 nm.…”
Section: Processing Micro/nano Perovskite Materialsmentioning
confidence: 99%
“…In this intricate process, the key determinants for the perovskite's final characteristics and performance include the carefully calibrated parameters of etching time, operating voltage, and current. 54 Li et al made a significant breakthrough by developing a hydration intermediate phase regulated epitaxy growth technique, which enabled the fabrication of highly oriented nano arrays on bulk perovskite MAPbI 3 SCs (Figure 2a). 51 The arrays exhibited a preference for growth along the (110) crystal plane, showcasing great potential for anticounterfeiting applications.…”
Section: Processing Micro/nano Perovskite Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9][10] Pb-based perovskites have the features of a large absorption coefficient, long exciton diffusion length, good defect tolerance, and low costs. [11][12][13][14][15] Many perovskites photodetectors with weak light detection capability have been explored. [16][17][18][19][20] For example, Wu et al reported a weak light detector based on MAPbI 3 nanowire and gained a large detectivity of 2.06 × 10 13 Jones, showing great potential in the field of reflection imaging.…”
Section: Introductionmentioning
confidence: 99%
“…Photodetectors based on ultraviolet (UV)-sensitive materials can detect UV light and convert it into electric signals that have widespread applications in optical communication, flame detection, and UV imaging. Inorganic wide-bandgap semiconductors have occupied the UV detection market for many years but face the bottlenecks of low flexibility and a limited material family . Although a series of low-dimensional wide-bandgap semiconductors have been designed to address this issue, their large-scale growth remains a challenge, limiting their practical application in industry .…”
mentioning
confidence: 99%